1990
DOI: 10.1021/jo00312a031
|View full text |Cite
|
Sign up to set email alerts
|

Polyene synthesis. Ready construction of retinol-carotene fragments, (.+-.)-6(E)-LTB3 leukotrienes, and corticrocin

Abstract: All products of the dirhodium tetraacetate catalyzed reactions of ethyl diazoacetate with furan, 2-methylfuran, 2,5-dimethylfuran, 2-ra-octylfuran, methyl furcate and methyl /3-(«-furyl)acrylate were isolated and characterized. They consist mostly of exo-cyclopropanecarboxylates and 1,4-diacyl-1,3-butadienes and some 3-(acylmethyl)furans. Treatment of the crude reaction mixtures with iodine or boron trifluoride furnishes 1,4-diacyl-1 (E) ,3 (E)-butadienes. Horner-Emmons condensation with the latter dicarbonyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…36 As this scaffold is an interesting and very convenient gateway for natural product synthesis it was extensively utilized to enter a several natural product families (Scheme 9). 64 provided an access to the core nuclei of trans seven-membered sesquiterpenes 66 (Xanthanolides).…”
mentioning
confidence: 99%
“…36 As this scaffold is an interesting and very convenient gateway for natural product synthesis it was extensively utilized to enter a several natural product families (Scheme 9). 64 provided an access to the core nuclei of trans seven-membered sesquiterpenes 66 (Xanthanolides).…”
mentioning
confidence: 99%
“…The diazomalonates for the cyclopropanation reaction were synthesized as follows (Scheme 3 and Table 1). Alcohols 11-14 were treated with the monoester of malonic acid 15a-b in the presence of dicyclohexylcarbodiimide and DMAP 19 The ability of the furan ring to participate in carbenoid insertion reactions is well known, 22,23 and indeed, the model studies confirmed this. Whereas in a model study, the phenyl substituted diazomalonate 22 upon treatment with catalyst 10c produced the corresponding cyclopropanolactone in 67% yield, the 3-furyl substituted diazomalonates were extensively decomposed with this catalyst.…”
Section: Resultsmentioning
confidence: 91%
“…14 For perspective, the United States consumed ~27 trillion cubic feet of natural gas in 2014. 15 However, sources of natural gas are often situated in remote locations such as the Bakken oil field in North Dakota where there is no adequate natural gas transportation infrastructure, 16 making it difficult and expensive to move natural gas to places where it can be used. 2 Pipelines provide the means to exploit some of this natural gas but have not been utilized to their fullest potential due to the great expense (between $30,000 and $100,000 per inch-mile-for example, a 24 inch diameter pipeline at $100,000 per inch-mile costs $2,400,000 per mile-between 1993…”
Section: Chemicals From Natural Gas and Petroleummentioning
confidence: 99%
“…15 Although it appeared that the major product from the deprotonation of 4 with NaHMDS was putative [C(pz) 4 ]Ru[P(OCH 2 ) 3 CEt](Cl)(4-chloroanilido) (7), the minor product was not identified. The reaction of 4 with LDA (lithium di(isopropyl)amide) (di(isopropyl)amine pK a = 40) 16 in THF-d 8 at -78 °C was performed; this reaction resulted in one new complex, the putative complex 7, that converted to a different complex overnight that was not identified or It would appear from these results that stronger bases such as LDA and NaH are necessary for clean deprotonation of 4.…”
Section: Initial Deprotonation Followed By Halide Abstractionmentioning
confidence: 99%
See 1 more Smart Citation